Evolutionary model for gradual transition to Integrated Project Delivery (IPD) - Denis Granja, A.; Muianga, E. Atália Daniel; Picchi, F. Augusto; Torres Formoso, C. (Revista Ingeniería de Construcción, 2023)
Over the years, construction projects have been developed and delivered through traditional delivery methods. However, traditional delivery methods have been considered ineffective to achieve the real project goals. Integrated and collaborative models, such as Integrated Project Delivery (IPD), a delivery method based on relational contracts, has attracted growing interest in both academia and industry, but still scarce in Architecture Engineering, and Construction (AEC). Most prior research emphasized the identification of barriers and challenges to implementing IPD and few studies focused on developing strategies to overcome those constraints. A limited number of studies have addressed how to reap the benefits of IPD in AEC environments where collaboration between stakeholders is poor. This research investigates how to integrate IPD into AEC projects when collaboration is still limited. An “IPD Evolutionary Model” and guidelines for its implementation were developed for applications in such environments. Design Science Research was the research approach adopted in this study to discuss and evaluate the proposed model. The model emphasizes an evolutionary and flexible process for the IPD application in AEC projects. The model postulates the desirable and required IPD elements according to the levels of application difficulty, emphasising stakeholders' readiness for using it and the gradual introduction of IPD in such environments.